Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fimmu.2018.01994
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal-Associated Invariant T Cells Improve Nonalcoholic Fatty Liver Disease Through Regulating Macrophage Polarization

Abstract: Mucosal-associated invariant T (MAIT) cells, a novel population of innate-like lymphocytes, have been involved in various inflammatory and autoimmune diseases. However, their role in the development of nonalcoholic fatty liver disease (NAFLD) remains unclear. In this study, we investigated the alterations of phenotype and immunological function of MAIT cells in NAFLD. Analysis of PBMCs in 60 patients with NAFLD and 48 healthy controls (HC) revealed that circulating MAIT cell frequency decreased in NAFLD, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(113 citation statements)
references
References 47 publications
5
102
0
1
Order By: Relevance
“…Stimulation with bacterial supernatants ex vivo confirmed previous studies on the dysfunctional nature of cMAIT cells as they responded with lower production of the proinflammatory cytokines TNF and IFN-g in response to bacterial stimulation, which is consistent with previous observations in chronic liver disease. 13,22 On the contrary, peritoneal cells from patients with advanced liver disease remained potent producers of IFN-g and TNF after stimulation with bacterial supernatants or phorbol myristate acetate/ionomycin. Having shown that MAIT cells differ in function and phenotype when compared with tissue resident MAIT cells 39 has important implications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation with bacterial supernatants ex vivo confirmed previous studies on the dysfunctional nature of cMAIT cells as they responded with lower production of the proinflammatory cytokines TNF and IFN-g in response to bacterial stimulation, which is consistent with previous observations in chronic liver disease. 13,22 On the contrary, peritoneal cells from patients with advanced liver disease remained potent producers of IFN-g and TNF after stimulation with bacterial supernatants or phorbol myristate acetate/ionomycin. Having shown that MAIT cells differ in function and phenotype when compared with tissue resident MAIT cells 39 has important implications.…”
Section: Resultsmentioning
confidence: 99%
“…13 Performing and interpreting such studies is challenging because the cMAIT cell pool is depleted in patients with liver disease, and conflicting data exist whether MAIT cells accumulate in the diseased liver. 13,[21][22][23] Because the depleted cMAIT cell pool may differ from organ-resident MAIT cells, the aim of this study was to investigate the phenotype and function of human MAIT cells in the peritoneal cavity in decompensated cirrhosis and during the course of SBP.…”
mentioning
confidence: 99%
“…In patients with nonalcoholic fatty liver disease (NAFLD), MAIT cells accumulate around fatty hepatocytes. Although mouse and human studies have demonstrated the profibrogenic properties of MAIT cells, Mr1 −/− mice fed a methionine-choline-deficient diet show enhanced steato sis, are more prone to liver injury and have more CD11c + M1-like inflammatory macrophages but fewer CD206 + M2-like macrophages 93 . Future studies will be needed to confirm this protective role of MAIT cells in a more relevant model of nonalcoholic steatohepatitis, and the contribution of IL-17 needs to be evaluated, as it is a major driver of NAFLD progression 132,133 .…”
Section: Prevention Of T1d By Mait Cellsmentioning
confidence: 98%
“…The decreased frequency of blood MAIT cells in immunemediated diseases could also result from their death by apoptosis subsequent to sustained activation. Accordingly, in many autoimmune and inflammatory diseases, circulating MAIT cells express higher levels of activation and/or exhaustion markers, such as CD38, CD25, CD69 and PD-1 (reFs 16,18,69,70,73,83,85,87,89,93 ). Furthermore, in some diseases MAIT cell activation correlates with disease activity score (TaBle 3).…”
Section: Presence Of Mait Cells In Inflamed Tissuesmentioning
confidence: 99%
See 1 more Smart Citation